THE INFLUENCE OF PERCEPTION ON LEARNING TECHNIQUES AND VOCABULARY MASTERY TOWARD ENGLISH WRITING ABILITY (Survey on Students of Public Vocational High School in Central Jakarta) - Annisa Farah; Doni Anggoro Ari Santoso (Universitas Indraprasta PGRI, 2022)
The purpose of this study is to determine the effect of learning technique and vocabulary mastery on the English writing ability of students of XI grade of Public Vocational High School in Central Jakarta. The research method used is quantitative research with correlational survey research techniques. The data analysis technique used in this research is Path Analysis. The population in this study was students of XI grade of Public Vocational High School (SMK Negeri) in Central Jakarta area. The sample in this study was 110 students. The results of the study prove that: (1) there is a significant influence of perception on learning technique toward English writing ability as indicated by the t-count = 1.865, (2) there is a significant influence of perception on vocabulary mastery toward English writing ability as indicated by the t-count value = 16,733, and (3) there is a significant influence of perception on learning technique and vocabulary mastery together toward the ability to write English as indicated by the value of F-count = 161.202. The results of this study can provide input to vocational level teachers, especially English teachers to improve their competence in order to develop learning techniques and improve students’ vocabulary mastery, so as to optimize students' English writing ability.